Development of redox-recyclable ion exchange materials for the removal and recovery of heavy metal contaminants from aqueous media - Dysleski, Lisa, author; Dorhout, P. K., advisor; Strauss, S. H., advisor; Levinger, N. E., committee member; Stermitz, F. R., committee member; Reardon, K. F., committee member (Colorado State University. Libraries, 2003)
Alkali metal or proton intercalated molybdenum disulfides, AxMoS2 (where A = H+, Na+, or K+ and x < 1.3) were investigated as redox-recyclable ion exchange extractants for the soft, aqueous metal ions Hg2+, Pb2+ and Ag+. The charge on the MoS2x- layers was successfully decreased from its initial value of 1.3- to 0 .80- by contacting Li1.3MoS2 with an aqueous solution of ANO3. The residual charge on the layers of the resulting solid was determined by hydrogen (H2) gas evolution and mass balance studies. The charge compensating cations were a combination of Li+ (from the original solid) and A+ from the reaction solution, depending on the initial reaction conditions. All of the molybdenum disulfide intercalates were found to have varying degrees of hydration. Upon drying under dynamic vacuum, however, only the Na+ and K+ analogs retained their hydration spheres. This resulted in a larger interlayer spacing, d, into which ion exchange with various heavy metal cations was facile. Proton intercalated MoS2 was found to decompose at approximately 100 °C, to form H2(g) and MoS2. The sodium and potassium analogs were stable to elevated temperatures (to 500 °C), however decomposed in acidic, aqueous solution to form HxMoS2. All of the above-mentioned extractants were found to be inappropriate for use at low pH. The thiospinels Cu2MSn3S8 (M= Fe, Mn) were also investigated as effective and stable ion exchange extractants for heavy metal cations. Metal ion extraction reactions were investigated using mass balance experiments and indicated exchange of both copper and transition metal ions out of the solid for soft heavy metal cations in solution. This ion exchange reaction was found to be both slow as well as incomplete with low ion removal over time periods up to 6 days, even in the presence of excess extractant. In addition, these extractants were shown to perform poorly in aqueous acid. In order to increase the thermodynamic driving force and decrease the kinetic barrier to ion exchange, it was desirable to introduce alkali metal cations such as lithium or sodium into the parent structures. In order to do this, cations were extracted from or inserted into the parent solids using chemical oxidation and reduction reactions. These reactions were typically limited to the surface of the powders, however, resulting in little oxidation or reduction of the bulk material. Therefore, direct synthetic methods were used to prepare the following new thiospinels: CuMnSn3S8; Cu2Sn3S8; CuFeSn3S8; Li2FeSn3S8; and LiCuFeSn3S8. The compounds Na2FeSn3S8 and NaCuFeSn3S8 were also synthesized, however these two solids did not crystallize with a spinel structure. Finally, new proton-activated thiospinels were also synthesized as potential metal ion extractants. Stoichiometries of the synthesized proton-activated iron compounds ranged from H0.10Cu1.90Fe0.97Sn3S8 to H0.18Cu1.90Fe0.96Sn3S8 depending on reaction conditions. In the case of the manganese analog, a material with a stoichiometry of H0.37Cu1.9Mn0.82Sn3S8 was synthesized. The degree of protonation depended on the contact time between the parent solid and an acidic solution. The type of acid used had little effect. In all cases, the alkali metal and proton intercalated thiospinels outperformed the parent spinel compounds in terms of total metal ion extracted as well as extraction time. Using mass balance experiments, the mechanism of metal ion removal with the proton activated thiospinels was shown to be ion exchange. The mechanism of ion extraction by alkali metal intercalates is, however, still unclear. Metal ion recovery from various spinels investigated showed that heating to 500 °C resulted in the release and recovery of reduced metal.
Keywords: chemistry; inorganic chemistry